The Influence of Knowledge-Oriented Leadership on Enhancing Innovative Green Work Behavior with Green Work Engagement as A Mediator - Sri Winarni (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2025)
Objective – This study investigates green HRM practices and knowledge-oriented leadership facilitating creative, green work in SMEs. This paper emphasizes the ways that sharing of leadership stimulates a green ideas climate. This type of leadership stimulates the sharing of knowledge, essential for green behavior, behaving as a coach encouraging the team with green and creative ideas. The emphasis here turns to